The Effect Of Value Clarification Technique Learning Model Based On Educational Adventure Game On Critical Thinking Skills For Elementary School Students - Afandi, Muhamad; Yustiana, Sari; Yulina, Yulina; Turahmat, Turahmat; Husaini, Ahmad; D. Pagal, Evangeline (IJORER : International Journal of Recent Educational Research, 2025)
Objective: The low critical thinking ability of students in Pancasila Education subjects causes them to only memorize materials without being able to analyze, evaluate, and solve problems critically. This study aims to apply the Value Clarification Technique (VCT) learning model based on Educational Adventure Game and analyze its effect on improving students’ critical thinking ability in Pancasila Education subjects. Methods: This study uses an experimental method (quasi-experimental design) with a sample of grade IV Elementary School students, and data collection is carried out quantitatively using a test instrument to measure critical thinking skills. Results: This study presents a novel approach by integrating the Value Clarification Technique (VCT) with Educational Adventure Games to enhance critical thinking in Pancasila Education an area that has traditionally focused more on rote memorization than analytical skill development. Based on the results of the hypothesis test at SD Negeri 1 Jeketro, the t-count value of 7.305 is greater than the t-table of 2.017 at a significance level of 95% with α = 0.01. The same results were also found at SD Negeri 1 Saban, where the t-count value of 7.205 is greater than the t-table of 2.017 at a significance level of 95% with α = 0.02. Conclusion: Thus, it can be concluded that the use of the Educational Adventure Game-based VCT learning model has a significant effect on improving students’ critical thinking skills in the Pancasila Education subject.